Deconstructing gendered glorification of charitable work: A case of women in Nomiya Church - Musili, Telesia K. (HTS teologiese studies, 2024)
Human immunodeficiency viruses (HIV) and acquired immunodeficiency syndrome (AIDS), COVID-19 and Ebola have exposed the magnitude of care-related tasks on women. Most often, because of the gendered nature of domestic and reproductive roles, women are expected to assume unpaid care-related, nurturing and domestic work. Despite the valuable duties, women are economically poor and othered. These unpaid care duties are exacerbated by pandemics and ratified even further by religion. For instance, in Nomiya Church (NC), the first African independent church in Kenya, women’s experience narratives and biblical texts such as the story of the Proverbs 31 virtuous woman are used to glorify unpaid charitable work for women. Women’s virtuous personality, hard work and character are upheld in Christian spaces, thus obstructing sound work theologies. This article employed African Women’s theological lens in view of pointing out repressing and transformative tenets in charitable theologies of work for social and gender justice. While applying womanhood hermeneutics in the passage, the article points to valued behavioural postures of hard work in responding to God’s stewardship mandate. An affirmation of fair reward and accumulation of property is embraced as a familial complementary role, especially in pandemic contexts. The article amplifies the accumulation of property as a human right and the mandate of stewardship for all earth communities. Hence, charity work is a stewardship framework that all earth communities must engage in for replenishment and sustenance for all.Contribution: The article challenges literal biblical interpretations that glorify charity work. It advances a stewardship framework in understanding unpaid and charity work that all earth communities must engage in to replenish and sustain all creation. The framework affirms the dignity of all human persons through a transformational understanding of the theology of work as enabled by the African theological hermeneutics.